Starting Your Career with a Temporary Job: Stepping Stone or "Dead-End"? - Dimitris Pavlopoulos (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper uses panel data from the UK (BHPS) and Germany (GSOEP) to investigate the wage effect of entering the labour market with a temporary job. Further than the previous literature that studied the effect of the contract type on wage dynamics in the explained part of a wage regression, we also investigate the effect of the starting contract on the variance of unobserved individual effects and random earnings shocks. For this purpose, we decompose earnings into a component determined by initial unobserved earnings ability and experience-related heterogeneity and a component determined by earnings shocks. Our results for Germany, verify the existence of a wage penalty for entering the labour market with a temporary contract. This penalty disappears after 12.5 years for male workers and after 6.5 years for the female workers. In the UK, a similar wage penalty is found for male workers that persists over their working career. In contrast, no wage penalty is found for the British female workers. In the UK, the initial unobserved earnings capacity is higher for workers starting off with a permanent job, while no such difference emerges in Germany. However, this initial unexplained wage inequality decreases faster for workers starting their career with a temporary contract than their colleagues that entered the labour market with a permanent job. Finally, the persistence of earnings shocks is higher for workers entering the labour market with a temporary contract.
Keywords: J31; J41; 330; temporary employment; wages